1977
DOI: 10.1139/f77-004
|View full text |Cite
|
Sign up to set email alerts
|

Development of Atlantic Salmon (Salmo salar) Eggs and Alevins Under Varied Temperature Regimes

Abstract: Atlantic salmon (Salmo salar) eggs and alevins were raised under conditions where the temperature was systematically varied either at fertilization, at the eyed egg stage, or at hatching. Mortality was more than 20% in eggs started immediately after fertilization at constant incubation temperatures < 4 °C as compared with 5% or less at temperatures > 4 °C. Alevins that eyed at 8 °C and higher were progressively smaller the higher the temperature. The optimum temperature from fertilization to eye pigmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 0 publications
7
78
0
1
Order By: Relevance
“…Within the literature incubation temperatures have been found to have a significant effect on the size of Pacific salmon throughout early development (Peterson 1977;Murray and McPhail 1988;Murray et al 1990), a finding consistent with my study. Lower incubation temperatures produce larger alevin and fry (Peterson 1977;Murray and McPhail 1988;Murray et al 1990). For coho salmon, alevin and fry were largest at 2 ºC (Murray and McPhail 1988), while Murray et al (1990) found fry to be largest at mid temperatures ranging from 4-8 ºC.…”
Section: Size and Condition Factorsupporting
confidence: 91%
“…Within the literature incubation temperatures have been found to have a significant effect on the size of Pacific salmon throughout early development (Peterson 1977;Murray and McPhail 1988;Murray et al 1990), a finding consistent with my study. Lower incubation temperatures produce larger alevin and fry (Peterson 1977;Murray and McPhail 1988;Murray et al 1990). For coho salmon, alevin and fry were largest at 2 ºC (Murray and McPhail 1988), while Murray et al (1990) found fry to be largest at mid temperatures ranging from 4-8 ºC.…”
Section: Size and Condition Factorsupporting
confidence: 91%
“…Other aspects affected by temperature are the yolk conversion efficiency as demonstrated in salmonid embryos (Heming, 1982;Heming and Buddington, 1988;Marr, 1996;Peterson & Martin-Robichaud, 1995) and in stripped bass (Peterson et al, 1996). Also larval size and fitness at the end of the endogenous feeding period are directly affected by temperature (Peterson et al, 1977, 1996, Baynes and Howell, 1996. Therefore, temperature has a key controlling effect on metabolic processes through thermal dependence on enzymatic activity (Brett, 1970;Rombough, 1988;Blaxter, 1992).…”
Section: Importance Of Temperature On Embryonic and Larval Developmentmentioning
confidence: 99%
“…It may be that this advance triggered the earlier onset of the hyperplastic event associated with increased incubation temperatures observed herein (Fig.·7). In species that have a long yolk-dependent stage, such as the 30-90 days for Atlantic salmon (Peterson et al, 1977) or the 50 days for halibut (Galloway et al, 1999), significant recruitment of deep muscle fibres was observed either towards the end of or following the complete absorption of the yolk (Johnston and McLay, 1997;Galloway et al, 1999). Within this yolkdependent larval stage, hypertrophy was the dominant process.…”
Section: Deep Myotomementioning
confidence: 99%